2003
DOI: 10.1124/dmd.31.8.1035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Primary Human Hepatocytes and Hepatoma Cell Line Hepg2 With Regard to Their Biotransformation Properties

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Cultures of primary hepatocytes and hepatoma cell line HepG2 are frequently used in in vitro models for human biotransformation studies. In this study, we characterized and compared the capacity of these model systems to indicate the presence of different classes of promutagens. Genotoxic sensitivity, enzyme activity, and gene expression were monitored in response to treatment with food promutagens benzo[a]pyrene, dimethylnitrosamine (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
400
1
9

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 676 publications
(418 citation statements)
references
References 37 publications
8
400
1
9
Order By: Relevance
“…These cells were selected as they express a range of xenobiotic-metabolising enzymes (36)(37)(38)(39)(40) as well as ERα and ERβ receptors (41). The HepG2 cells were provided by Professor Firouz Darroudi (Leiden University Medical Centre, Department of Toxicogenetics, Leiden, The Netherlands).…”
Section: Human Hepg2 Cellsmentioning
confidence: 99%
“…These cells were selected as they express a range of xenobiotic-metabolising enzymes (36)(37)(38)(39)(40) as well as ERα and ERβ receptors (41). The HepG2 cells were provided by Professor Firouz Darroudi (Leiden University Medical Centre, Department of Toxicogenetics, Leiden, The Netherlands).…”
Section: Human Hepg2 Cellsmentioning
confidence: 99%
“…19,20,23 However, HepG2 cells lack the full expression of hepatocyte proteins, such as phase I and phase II metabolizing enzymes and transporters, and thus may not correlate to in vivo hepatotoxicity. [24][25][26] As an alternative to HepG2 cells, primary human hepatocytes represent the best predictive in vitro model to determine liver function for metabolism, 27,28 drug-drug interactions, 29,30 and potential hepatotoxicity of compounds. [30][31][32] Hepatocytes can be utilized in suspension for assays lasting a few hours or may be maintained in collagen-coated tissue culture plates for extended culturing.…”
Section: Introductionmentioning
confidence: 99%
“…drug and ammonia metabolism, in vitro compared with primary counterparts, thereby limiting their application in the support system (Cascio 2001). Furthermore, comparison of primary human hepatocytes and the hepatoma cell line (HepG2) has shown that the former are more suitable for the development of liver support systems with respect to their biotransfomation properties (Wilkening et al 2003). Expansion of autologous hepatocytes in patients with liver disease is not advantageous for at least the following five reasons: (i) The underlying disease, i.e.…”
Section: Cell Sourcementioning
confidence: 99%